Association of fusarium wilt susceptibility with clubroot resistance derived from winter Brassica napus L. 'Mendel'. Issue 1 (2nd January 2019) - Rahman, Habibur; Franke, Coreen
Abstract: The development of canola cultivars with resistance to soil-borne diseases, such as clubroot and fusarium wilt, is important for successful production of this crop. A clubroot resistance gene on the A3 chromosome of the European winter Brassica napus L. cultivar 'Mendel' has been introgressed into Canadian spring canola for the development of clubroot resistant cultivars. However, the spring canola lines carrying this resistance were found to be susceptible to fusarium wilt disease, which is an impediment for use of this resistance source in breeding. Clubroot and fusarium wilt resistance were analysed using a doubled haploid (DH) population derived from crossing spring canola lines carrying 'Mendel'-based clubroot resistance with canola lines resistant to fusarium wilt. This analysis showed that a Mendelian gene was involved in the control of resistance to each disease. However, testing for independent assortment of these two traits showed a significant deviation from the expected 1:1:1:1 segregation, indicating that a genetic linkage exists between the loci governing resistance to these two diseases. The occurrence of about 10% of the lines with recombinant phenotypes suggested that these two loci are located about 10 cM apart; this demonstrates the possibility of developing a canola line carrying resistance to both diseases.